Humanitarian Expertise As A Tool For Creating The Image Of Well-Being Future; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 38 : Lifelong Wellbeing in the World (WELLSO 2017) - Lankin V. G. (2018, 2018)
Title screen